Detection of Virulence-Associated Genes and in vitro Gene Transfer From Aeromonas sp. Isolated From Aquatic Environments of Sub-himalayan West Bengal - Mangar, Preeti; Barman, Partha; Kumar, Anoop; Saha, Aniruddha; Saha, Dipanwita (Frontiers in Veterinary Science, 2022)
Aeromonas is omnipresent in aquatic environments and cause disease within a wide host range. A total of thirty-four isolates from water samples of small fish farms were identified as Aeromonas based on biochemical characteristics and 16S rRNA gene sequence. A total of six virulent factors were analyzed which indicated 100% of isolates as beta-haemolytic and proteolytic, whereas 44.1, 38.2, and 70.6% of isolates produced DNAse, siderophore, and amylase, respectively. Studies on the occurrence of four genetic determinants of virulence factors revealed that aer/haem (haemolytic toxin) and flaA (polar flagella) genes were present in 44.1% of strains whereas ascV (type 3 secretion system) and aspA (serine protease) genes were detected in 21.5 and 8.82% of strains, respectively. Fish (Anabas testudineus) challenge studies showed that the isolate GP3 (Aeromonas veronii) bearing five virulent factors with the combination of aer/haem+/ascV+/fla+ genes induced severe lesions leading to 100% of mortality. In contrast, RB7 possessing four virulence factors and three genes (aer/haem+/ascV+/aspA+) could not produce severe lesions and any mortality indicating the absence of correlation between the virulence factors, its genes, and the pathogenicity in fishes. GP3 was cytotoxic to human liver cell line (WRL-68) in trypan blue dye exclusion assay. The 431 bp aer/haem gene of GP3 was transferable to E. coli Dh5α with a conjugational efficiency of 0.394 × 10–4 transconjugants per recipient cell. The transfer was confirmed by PCR and by the presence of 23-kb plasmids in both donor and transconjugants. Therefore, the occurrence of mobile genetic elements bearing virulence-associated genes in Aeromonas indicates the need for periodic monitoring of the aquatic habitat to prevent disease outbreaks.